Vitamin D status in children with mild, moderate, or severe confirmed COVID-19: systematic-review and meta-analysis - Mousavi, Tahoora; Moosazadeh, Mahmood (Frontiers in Pediatrics, 2025)
BackgroundVitamin D acts as a pro-hormone with a wide range of beneficial effects. It is reported that vitamin D deficiency is a risk factor for COVID-19 severity in children. In the present study, we decided to assess 25 hydroxy (OH) vitamin D status in children with mild, moderate, or severe confirmed COVID-19 and also compare them with those of a healthy control group using existing data.MethodsRelevant studies were extracted using online international databases including Scopus, Science Direct, PubMed, Web of Science, ProQuest, and Google Scholar search engine between Jan 2019 and 2024. The quality of all papers is determined by the NOS checklist. Heterogeneity between the results of primary studies was evaluated with the I-square index. Egger's test, funnel plot, and sensitivity analysis were applied. The statistical analysis was done using Stata version 17.ResultsIn 12 documents, the status of vitamin D was examined between case and control groups. By combining the results of these studies using random effect model, the standardized mean difference (SMD) vitamin D level in the COVID-19 children compared to the control group was estimated to be −0.88 (98% CI: −1.24, −0.51), which was statistically significant. In the present study, the odd ratio of vitamin D deficiency and vitamin D disorder (insufficiency and deficiency) in children with moderate COVID-19 compared to asymptomatic children with COVID-19 were estimated to be 3.58 (1.10, 11.63) and 2.52 (0.99, 6.41) respectively which was higher than in asymptomatic children with COVID-19. In addition, vitamin D deficiency and vitamin D disorder in children with moderate COVID-19 compared to the children with mild COVID-19 were estimated to be 2.12 (0.90, 4.98) and 1.82 (0.78, 4.22) respectively, which was higher than in children with mild COVID-19. Also, vitamin D deficiency and vitamin D disorder in children with mild COVID-19 compared to asymptomatic children with COVID-19 were estimated to be 2.02 (0.60, 6.78) and 1.64 (0.53, 5.07) respectively, which was higher than in asymptomatic children.ConclusionsCombining the results of these studies, the effect size of the relationship between vitamin D and COVID-19 in children is significant. During the COVID-19 pandemic (except for the Omicron peak), children were less affected by the severity of COVID-19. The standardized mean difference (SMD) vitamin D level in children with COVID-19 was significantly 0.88 units lower than the control group. Also, the odds ratio of moderate COVID-19 in children with vitamin D deficiency was significantly 3.58 times higher than in asymptomatic children with COVID-19.